(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
This essay illustrates the content of the articles of the codes of ethics of doctors (2014), of the two nursing professions (2019) and of fifteen health professions belonging to the National Federation of the Orders of Medical Radiology Technicians and of the Technical, Rehabilitation and Prevention Health Professions, which regulate the participation of the professionals to whom they refer in the shared care planning (PCC). Article 5 of Law No. 219 of 2017 does not mention health professionals other than doctors among those who participate in the development of the PCC. The articles of the codes of ethics consider the peculiar role appropriately assumed, as members of the healthcare team, by various professionals in said development.